الأبعاد الفلسفية في قصة حي بن يقظان لابن طفيل "دراسة تحليلية في المعرفة والوجود والإنسان" (Comprehensive Journal of Science, 2025)
Hayy ibn Yaqzān by Ibn Ṭufayl represents a pioneering philosophical model within the Islamic intellectual tradition, integrating epistemology, ontology, and ethics into a unified conceptual framework. This study aims to analyze the philosophical dimensions of the narrative, focusing on the epistemological, ontological, and ethical structures, while exploring Ibn Dufay’s methodological approach in shaping the protagonist’s consciousness and linking knowledge to moral conduct. Epistemologically, the study highlights how Hayy begins his intellectual journey through sensory observation and individual experience, gradually moving toward rational inference and ultimately ascending to spiritual unveiling and illuminative intuition. This progression reflects a hierarchical vision of knowledge that synthesizes the sensory, rational, and spiritual faculties. Ontologically, the text portrays the human being as a dual entity composed of the physical body and the transcendent soul, advancing in understanding the cosmos from natural phenomena to the realization of the First Principle. This model aligns with the concepts of the gradual intellect and Illuminations philosophy within the broader Islamic philosophical heritage. Ethically, the narrative demonstrates that moral action is the natural outcome of intellectual and existential elevation. Virtue is shown to arise from heightened awareness, with moderation, ascetic discipline, and control of desires functioning as essential mechanisms for achieving mental clarity and spiritual refinement. The text also addresses the relationship between the individual and society, emphasizing the importance of tailoring ethical guidance according to the varying capacities of individuals to apprehend truth—a reflection of Ibn Dufay’s advanced pedagogical and philosophical insight. The study concludes that Hayy ibn Yaqzān is not merely a literary work, but a comprehensive philosophical project combining reason, experience, and spiritual intuition. It contributes significantly to understanding the human condition, the individual’s place in the cosmos, and the dynamics of human relationships. Moreover, the narrative retains contemporary relevance in fields such as philosophy of education, philosophy of science, and moral philosophy, offering a rich conceptual lens through which to reflect on the interrelation between knowledge, ethical action, personal experience, and collective human development.
Keywords: Ibn Ṭufayl, Hayy ibn Yaqzān, epistemology, ontology, reason, Islamic philosophy.